2015
DOI: 10.1108/mf-08-2013-0222
|View full text |Cite
|
Sign up to set email alerts
|

Directors’ remuneration, governance and performance: the case of Malaysian banks

Abstract: Purpose – The purpose of this paper is to examine the association between directors’ remuneration and performance and corporate governance in the Malaysian banking sector, using panel data for 21 banks over the period 2003-2011. Design/methodology/approach – The authors use multivariate regression analysis to examine the relationship between directors’ remuneration and performance and corporate governance. The authors also run Granger ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 58 publications
4
36
3
1
Order By: Relevance
“…After regressing the control variables, the positive impact of DCOMP held. This is consistent with the findings of Peng and Mansor (2015), Doucouliagos et al (2007), Brian et al (1996), Jaafar et al (2011), and Ghosh (2006), as well as the agency theory (Fama 1980). Our study further suggests that the compensation paid to directors in Pakistan is consistent with past bank performance; therefore, it has a positive impact on profitability 12 .…”
Section: Board Findingssupporting
confidence: 92%
See 3 more Smart Citations
“…After regressing the control variables, the positive impact of DCOMP held. This is consistent with the findings of Peng and Mansor (2015), Doucouliagos et al (2007), Brian et al (1996), Jaafar et al (2011), and Ghosh (2006), as well as the agency theory (Fama 1980). Our study further suggests that the compensation paid to directors in Pakistan is consistent with past bank performance; therefore, it has a positive impact on profitability 12 .…”
Section: Board Findingssupporting
confidence: 92%
“…We found a significant positive impact of lagged bank profitability, when measured by ROA, ROE, and PM, on director compensation and an insignificant positive impact of lagged director compensation on profitability, indicating that, in Pakistan, director compensation is explained by past bank performance. Our findings contradictBugeja et al (2016) andPeng and Mansor (2015), who both found an inconsistent relationship between past performance and director compensation. The results of the Granger causality are not reported, but are available upon request.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Directors' remuneration is one of the motivation mechanisms for the directors in order to help their company achieve, maintain and driven board motivation to improve firm value. Several studies found that higher remuneration paid to the board of directors leading to higher financial performance (Lee & Isa, 2015). On the other hand, other studies found a negative relationship between board remuneration and firm performance (Hassan & Theo, 2003).…”
Section: Independent Variablesmentioning
confidence: 93%